A novel way to optimize the process parameters by integrating the grey relational coefficient and the combined compromise solution for machining the CFRP composites - K. Shunmugesh; Arun Raphel; Sony Kurian; Shivashankarayya Hiremath; Gajanan Anne; B. R. N. Murthy; H. M. Vishwanatha (Scientific Reports, 2025)
Abstract The quality of carbon fiber-reinforced plastic (CFRP) machining during wet drilling is strongly influenced by the moisture content and cutting tool geometry. The current investigation aims to determine the optimum drilling process parameters for machining CFRPs by combining the grey relational coefficient with the combined compromise solution (Grey-CoCoSo). A distance correlation-based criterion importance through intercriteria correlation (D-CRITIC) method was used to ascertain the weights of decision-making to manage the responses from multiple-measure decision-making. Several multiresponse outputs—the material removal rate (MRR), surface roughness (Ra), and delamination factor (DF)—were taken into consideration during the analysis of the input factors—the spindle speed (N), drill diameter (D), and feed rate (F). An enhanced MRR and reduced Ra and DF were achieved due to the optimal parametric conditions of D, F, and N when the D-CRITIC weight was set to 6 mm, 0.1 mm/rev, and 7500 rpm, respectively. As a result, the Ki value would have improved by 17.684%. Thus, N was found to be a pivotal parameter influencing MRR, DF, and Ra. The outcomes indicate that the proposed synergistic approach is beneficial for solving situations in which multicriteria decision-making is applicable to CFRPs. Compared with other conventional multicriteria decision-making approaches, the proposed newer approach is versatile and efficient in excluding variation. Thus, the grey-CoCoSo approach can be a promising way of optimizing process parameters for machining CFRPs.